2021
DOI: 10.1111/jan.14810
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with family functioning in patients with heart failure and their family members: An international cross‐sectional study

Abstract: Aims: To describe and compare family functioning, family health, and perceived social support from nurses and to identify the variables that are associated with family functioning in patients with heart failure (HF) and their family members in Denmark,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“… 36 In addition, family functioning differs by cultural influence for families with patients. 37 In Chinese context deeply influenced by Confucianism, family is attached great importance in terms of providing care and support for members with disease. 38 In the present study, participants reported a moderate level of family functioning, which contributed to their moderate level of psychosocial adaptation.…”
Section: Discussionmentioning
confidence: 99%
“… 36 In addition, family functioning differs by cultural influence for families with patients. 37 In Chinese context deeply influenced by Confucianism, family is attached great importance in terms of providing care and support for members with disease. 38 In the present study, participants reported a moderate level of family functioning, which contributed to their moderate level of psychosocial adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nuclear families, the advantage of lineal families is intergenerational mutual aid. Moreover, good family functioning can promote mutual support among family members and increase the participation of family members (Shamali et al, 2021), which promotes family members to use human resources and civilian organizations' assistance, so as to improve the quality of home‐based care.…”
Section: Discussionmentioning
confidence: 99%
“…Disabled older adults requiring care are extremely dependent on families, and Chinese family members tend to view caring for disabled older adults as their obligation. Moreover, good family functioning can promote the health of family members (Shamali et al, 2021). Hence, family functioning plays an important role in the long‐term care for disabled older adults.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wong et al, 27 social support offered by family members, relatives, or friends promotes families’ ability to cope with and readapt to life challenges. Shamali et al 28 demonstrated that social support was positively associated with family functioning. Thus, social support was conducive to improving family resilience.…”
Section: Relationships Among Social Support Individual Resilience Fam...mentioning
confidence: 99%